The Mediterranean Diet 2011
DOI: 10.1002/9781118785027.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Constituents and Physiological Effects of Mediterranean Plant Foods

Abstract: Mediterranean plant foods are major sources of many essential nutrients including dietary fibre, essential fatty acids, various minerals including potassium, calcium and selenium, a wide range of vitamins (B vitamins, folate, vitamin C, provitamin A) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…This also has implications for implementation as a potential treatment option in the future. Each of the phytochemicals discussed here are found abundantly within a Mediterranean diet, as is tryptophan [ 35 , 36 , 38 ]. This provides additional support for the examination of this diet model and similar models in the remaining three studies [ 26 , 27 , 28 ] that showed positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This also has implications for implementation as a potential treatment option in the future. Each of the phytochemicals discussed here are found abundantly within a Mediterranean diet, as is tryptophan [ 35 , 36 , 38 ]. This provides additional support for the examination of this diet model and similar models in the remaining three studies [ 26 , 27 , 28 ] that showed positive outcomes.…”
Section: Discussionmentioning
confidence: 99%